2021
DOI: 10.1002/ejp.1727
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness and tolerability of carbamazepine and oxcarbazepine in 354 patients with trigeminal neuralgia

Abstract: Background: We aimed at evaluating the differential involvement of large myelinated Aβ-, small myelinated Aδ-, and unmyelinated C-fibers in patients with diabetic polyneuropathy and how they contribute to neuropathic pain. Methods: We collected clinical and diagnostic test variables in 133 consecutive patients with diabetic polyneuropathy. All patients underwent Aβ-fiber mediated nerve conduction study, Aδ-fiber mediated laser-evoked potentials and skin biopsy mainly assessing unmyelinated C-fibers. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
1
28
2
Order By: Relevance
“…Despite their effectiveness, the use of both medications is often limited by their side effects, which include drowsiness, dizziness, rash, ataxia, elevated liver enzymes, hematologic dyscrasias, and hyponatremia. A recent study demonstrated that oxcarbazepine might be better tolerated than carbamazepine, although any side effects may be seen with either medication [ 105 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Despite their effectiveness, the use of both medications is often limited by their side effects, which include drowsiness, dizziness, rash, ataxia, elevated liver enzymes, hematologic dyscrasias, and hyponatremia. A recent study demonstrated that oxcarbazepine might be better tolerated than carbamazepine, although any side effects may be seen with either medication [ 105 ].…”
Section: Treatmentmentioning
confidence: 99%
“…9 A recent study showed a higher frequency of treatment refractoriness in patients with idiopathic and secondary TN than in patients with classical TN. 10 Other drugs, such as lamotrigine, gabapentin, and phenytoin, can be considered in patients with a suboptimal response or toxicity to first-line pharmacologic treatment. Oftentimes, these medications are given as an add-on to first-line treatment despite there not being comparative studies between first-line monotherapy and combination therapy.…”
Section: Novel Ways Of Approaching the Pharmacologic Treatment Of Tri...mentioning
confidence: 99%
“…Oxcarbazepine is often used initially given its relatively better drug tolerability and a decreased potential for drug interaction compared to carbamazepine 9 . A recent study showed a higher frequency of treatment refractoriness in patients with idiopathic and secondary TN than in patients with classical TN 10 . Other drugs, such as lamotrigine, gabapentin, and phenytoin, can be considered in patients with a suboptimal response or toxicity to first‐line pharmacologic treatment.…”
mentioning
confidence: 99%
“…Carbamazepine, as the first-line drug at present, can effectively relieve the pain. However, after taking it for a long time, the curative effect will decrease, and the patient finally stops taking the medicine because of the pain that cannot be tolerated and seek surgical treatment ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%